Thor : tales of Asgard,. The challenge! - Lee, Stan. 1922-2018 (Spotlight, a division of the ABDO Group, 2014)
"An adaptation, in graphic novel form, of comic books revealing the adventures of the Norse gods and Thor before he came to Earth, featuring the relationship between young Thor and his scheming half-brother, Loki"--Publisher.